1960
DOI: 10.4141/cjps60-068
|View full text |Cite
|
Sign up to set email alerts
|

The Growth, Nicotine and Phosphorus Content of Tobacco Grown at Different Soil Temperature, Moisture and Phosphorus Levels

Abstract: Growth, nicotine and phosphorus content of tobacco, as influenced by soil temperature, soil moisture and soil phosphorus levels, were investigated by growing the flue-cured variety Hicks in a combination of three soil temperature, four soil moisture, and three soil phosphorus treatments.Soil temperature of 22 °C. and soil moisture of 75 per cent of available moisture appeared to be the best for the over-all growth of tobacco. The over-all growth was a little lower at the 30 °C. soil temperature than at the 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1963
1963
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Excessive K can also delay ripening, while high levels of P can cause leaf thickening and ultimately reduce yield (Tso, 1999). Excessively high levels of K will not affect yield but will limit nicotine production (Chaplin and Miner, 1980; Vann et al, 2012), and soil P content does not affect nicotine (Lolas et al, 1979; Parups et al, 1960). Studies involving B, Ca, Cl, and Fe indicate that these nutrients do not affect nicotine concentrations (Gaines et al, 1976; McCants and Woltz, 1967; Neas, 1961).…”
Section: Fertilization and Irrigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive K can also delay ripening, while high levels of P can cause leaf thickening and ultimately reduce yield (Tso, 1999). Excessively high levels of K will not affect yield but will limit nicotine production (Chaplin and Miner, 1980; Vann et al, 2012), and soil P content does not affect nicotine (Lolas et al, 1979; Parups et al, 1960). Studies involving B, Ca, Cl, and Fe indicate that these nutrients do not affect nicotine concentrations (Gaines et al, 1976; McCants and Woltz, 1967; Neas, 1961).…”
Section: Fertilization and Irrigationmentioning
confidence: 99%
“…Maintaining leaf turgidity is important for optimal growth, and thus is important for nicotine production (Tso, 1999). However, mild drought stress in the roots has been shown to increase nicotine synthesis (Parups et al, 1960). Ismail and Long (1980) demonstrated that the effects of drought stress and higher fertilizer N rates could be combined to significantly increase nicotine concentrations.…”
Section: Fertilization and Irrigationmentioning
confidence: 99%
“…The effects of soil temperature upon nutrient availability, and upon subsequent plant growth, have been investigated only recently. Such investigations have been made by Nielsen et al ( 5), Lingle and Davis ( 1, 4), Parups and coworkers (7,8), and various investigators in Russia (2,3). The study herein reported was conducted to determine the effect of soil temperature upon spring barley growth and response to P fertilization on soils varying in NaHC0 3soluble P.…”
mentioning
confidence: 88%